STRATEGI KEPALA SEKOLAH SEBAGAI INSTRUCTIONAL LEADER DALAM PENGUATAN KINERJA GURU DI SMP SWASTA AN-NIZAM MEDAN - Adhli Maulana; Abdul Fattah Nasution (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the strategy of the school principal as an instructional leader in strengthening teacher performance in the aspects of learning planning, implementation, and assessment at An-Nizam Private Junior High School, Medan. The study employed a descriptive qualitative method, with the principal, vice principals and teachers as informants; data were collected through semi-structured interviews, participant observation, and documentation studies, then analyzed using the Miles and Huberman model, with data validity tested through source, method, and theory triangulation. The findings show that the principal implements a planning strategy through aligning curriculum perceptions and developing Teaching Modules/In-Depth Learning Plans (RPM) based on the deep learning approach, an implementation strategy through layered supervision and the use of learning technology, and an assessment strategy through the digitalization of evaluation and the integration of cognitive, affective, and spiritual values. The novelty of this study lies in the finding of the Samisamo/SAMI-SAMO (One week-One modules) weekly monitoring program as a local innovation that effectively eases teachers' administrative burdens, as well as the integration of the deep learning approach within the instructional leadership framework at an Islamic-based school, which has not been widely explored in previous studies on instructional leadership.